Refugee Narratives Fluchtgeschichten - Ramsey-Kurz, Helga; Reckinger, Gilles (bricolage, 2020)
This bricolage of notes, sketches, stories, dialogues and reflections is the result of an interdisciplinary experiment based on encounters between students either of English or European Ethnology at the University of Innsbruck and refugees from Syria, Afghanistan and Pakistan. It documents how regular conversations and attentive listening enable a form of transcultural narration that breaks with dominant ways of recounting refugees' experiences.; Diese bricolage von Notizen, Skizzen, Geschichten, Dialogen und Reflexionen ist das Ergebnis eines interdisziplinären Experiments, das auf Begegnungen von Studierenden der Innsbrucker Institute für Anglistik und Europäische Ethnologie mit Geflüchteten aus Syrien, Afghanistan und Pakistan aufbaut. Sie dokumentiert, wie regelmäßige Gespräche und aufmerksames Zuhören ein transkulturelles Erzählen ermöglicht, das mit dominanten Fluchtnarrativen bricht.